Implementation of MOORA Method in Evaluating Work Performance of Honorary Teachers - Fadli, Sofiansyah; Imtihan, Khairul (Sinkron : jurnal dan penelitian teknik informatika, 2019)
Teachers posses an essential role in advancing schools and students. Therefore, the quality of teachers holds a significant aspect since their main tasks are to educate, teach, guide, direct, train, assess and evaluate students. That being said, having professional teachers and teaching staff is compulsory for schools in order to implement quality education processes. For this reason, schools always encourage improvement of teachers’ work performance and hence improve the quality of the management system of teaching staff by monitoring teachers’ work in implementing their tasks so that they can achieve the predetermined competency standards. Central Lombok Regency is one of the regencies in the Province of West Nusa Tenggara (NTB) with a total of 18 state high schools (SMAN) and a large number of honorary teachers. This study aims to develop a decision support system to facilitate the process of teacher performance evaluation using the MOORA method. Previously, the evaluation was performed manually based on direct observations by principals wherein they appointed potential teachers based on the evaluation criteria of honorary teacher performance. Such method is considered ineffective since it could cause internal conflicts among teachers and might cause some parties feel disadvantaged. To prevent this from happening, a system that can help in the process of evaluating teacher performance is necessary where the results can be used as references or recommendations for school principals. The first step taken is finding supporting data as mandated by The Minister of National Education Regulation No. 16 of 2007 on Academic Qualification Standards and Teacher Competency Standards. The criteria used in evaluating work performance of teachers are based on pedagogical, personality, social, and professional competence, with sub criteria. The data is then analyzed using (1) the Analytical Hierarchy Process (AHP) method to determine the weight of each competency, and (2) the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method to determine the highest alternative value or the highest performance value of honorary teachers based on a predetermined weight by processing the ranking. The ranking method is expected to be used as a solution in determining the honorary teacher who has the best performance based on the weight multiplication ranking of each criterion. The implementation of the decision support system using the AHP and MOORA methods can facilitate the process of evaluating the performance of honorary teachers so that the results can be adopted as a reference for school principals in providing recommendations for outstanding teachers who deserve to be promoted.